Polymer-Dispersed Liquid Crystal Gas Sensor for Acetone Detection Using Correlated Laser Speckles - Xiaoquan Bai; Ning Bu; Yuxiang Yan; Yifei Ma; Mei Wang; Suotang Jia; Xuyuan Chen; Zhaomin Tong (Photonic Sensors)
Abstract Acetone is a widely used volatile organic compound in various industries, and several gas sensors have been developed for its detection and real-time monitoring. This study reported a novel method for determining the acetone vapor concentration based on correlated laser speckles using polymer-dispersed liquid crystals (PDLCs). Here, PDLC films comprising a mixture of the thermotropic nematic liquid crystal (LC) and ultraviolet-curable polymers were fabricated using different LC mass ratios and ultraviolet curing conditions. The laser beam was transmitted through the PDLC film to generate scattered light and speckles. When the PDLC film was exposed to the acetone vapor, the acetone molecules diffused into the PDLC film and interacted with the LC molecules, modifying the orientation of the LC molecules and the equivalent refractive index of the LC droplets. This in turn decreased the correlation coefficient of the speckle images. The experimental results indicated that the PDLC gas sensor was selectively sensitive to different concentrations of the acetone vapor, ranging from 1 800 ppm to 3 200 ppm. In comparison with traditional LC gas sensors that use a polarizing microscope to detect the change in brightness of the modulated light field, the proposed method is simpler, less expensive, and more robust under external disturbances such as vibrations.